The first species of Eutheia Stephens from sub-Himalayan India (Coleoptera, Staphylinidae, Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2025)
Eutheia boreoindica sp. nov. is described based on a male collected in Uttarakhand, northern India. This is the third sub-Himalayan species, the two previously known ones are distributed in Pakistan and Nepal. Distribution of eastern Palaearctic species of Eutheia is summarized.